Kadar Protein Daging Pada Keturunan Puyuh (Coturnix coturnix japonica L.) Betina (F1) Dari Induk Yang Diberi Suplemen Serbuk Kunyit Dalam Pakan - Rifa'i, Ahmad; Saraswati, Tyas Rini; Tana, Silvana (Bioma : Berkala Ilmiah Biologi, 2016)
This research aims to review determine protein level of meat tillers (F1) quails female breederwas treated supplemented turmeric powdersin feeds. This research using an experimental method with completely randomized design (CRD). The animals test used 45 tillers quail female its breederwas treated supplements turmeric powders, divided in 3 (three) treatment, i.e. K0: Tillersquails female which breeder was not treated supplements turmeric powders in feed. K1: Tillersquails female which breeder was treated turmeric powder 54 mg/head/day in feed. K2: Tillersquails female which breeder was treated turmeric powder 108 mg/head/day in feed. Tillersjapanese quail not given any treatment, only the standard feed and maintained until 60 days. Data is taken from meat protein content, daily feed intake and body weight. Data were analyzed with analysis of variance (ANOVA) with assisted program SPSS 16, the results show a real difference, then continued with Duncan test with 95% confidence level (Î±=0.05). The results showed that effect of turmeric powder on breeder can lower daily feed intake, but can increase the protein content of the meat, so the feed efficiency is increased in tillers japanese quails female of breeder was treated turmeric powder.Â Keywords: Coturnixcoturnix japonica L.,Meat protein content, Japanese quail, Turmeric powder.